2014
DOI: 10.4081/jlimnol.2014.965
|View full text |Cite
|
Sign up to set email alerts
|

Predicting aquatic macrophyte occurrence in soft-water oligotrophic lakes (Pyrenees mountain range)

Abstract: Distribution of aquatic macrophytes in lakes is related to geographical, morphological, catchment and water chemistry variables as well as human impacts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Due to the fact that the majority of natural ponds occur at high altitudes with low or no human impact and all of them are oligotrophic, while artificial ponds are on the opposite end of the gradient, it is likely that mainly natural environmental factors related to altitude are responsible for different species richness of both groups. Our results confirmed that altitude and correlated proximate environmental variables are among the most significant predictors of macrophyte richness [8,9,13].…”
Section: Species Richness and Composition And Their Relation To Envirsupporting
confidence: 76%
See 2 more Smart Citations
“…Due to the fact that the majority of natural ponds occur at high altitudes with low or no human impact and all of them are oligotrophic, while artificial ponds are on the opposite end of the gradient, it is likely that mainly natural environmental factors related to altitude are responsible for different species richness of both groups. Our results confirmed that altitude and correlated proximate environmental variables are among the most significant predictors of macrophyte richness [8,9,13].…”
Section: Species Richness and Composition And Their Relation To Envirsupporting
confidence: 76%
“…3). Several studies from the mountain regions across Europe showed similar results: high mountain ponds and lakes offer conditions that are too harsh for the development of macrophyte vegetation, and the presence and diversity of macrophytes in these habitats is rare and low, respectively [11,13]. Artificial ponds with more appropriate climatic conditions compared to those at high altitudes, intensity of human impact, and subsequently higher nutrient supply can provide convenient space for macrophyte vegetation [7].…”
Section: Species Richness and Composition And Their Relation To Envirmentioning
confidence: 49%
See 1 more Smart Citation
“…However, our study lends further support to this evidence and highlights the need for further investigations. Indeed, the majority of both earlier and more recent works on this topic focused predominantly, or even exclusively, on water conditions when analyzing macrophyte patterns, neglecting the potential role of sediment (Kolada, 2010;Alahuhta, 2015;Lukács et al, 2015;Pulido et al, 2015). Furthermore, previous investigations that did analyze the depth distribution of macrophytes often included depth among the environmental determinants tested, thereby limiting the analytical potential of the studies and references therein), or used data mainly from shallow ecosystems (Søndergaard et al, 2013).…”
Section: Environmental Determinantsmentioning
confidence: 99%
“…Their plant community diversity varies from low to moderately high. Overall, these lakes support a range of freshwater plant communities that are rare in Europe and a number of very rare plant species, particularly isoetids (Rørslett, 1991;Pulido et al, 2012Pulido et al, , 2015. In this group of lakes, an important factor differentiating plant communities is the water acidity/alkalinity (Vestergaard and Sand-Jensen, 2000;Chmara et al, 2014).…”
Section: Introductionmentioning
confidence: 99%